Pengamatan Struktur Internal Organ Reproduksi Tumbuhan Gymnospermae dan Angiospermae pada Bunga Bakung (Hippeastrum sp.), Pinus (Pinus merkusii), serta Pengamatan Preparat Awetan Organ Reproduksi Jagung (Zea mays) - Salma Humairo; Saskia Asila Zahwa; Tatang Hernawan; Tifani Siti Fatiah; Yasmin Pajrin Maulani; Ita Fitriyyah (Tumbuhan : Publikasi Ilmu Sosiologi Pertanian Dan Ilmu Kehutanan, 2024)
Seed plants or spermatophytes are divided into two, namely angiosperms (open seed plants) and gymnosperms (closed seed plants). These seeds are a means of generative development of spermatophytes. This research aims to observe the internal structure of the reproductive organs of seed plants and observe the phases of embryo development in seed plants.  The method used is observing the structure of internal plant organs and is supported by literature studies related to the research carried out. The objects of this research are lilies (Hippeastrum sp.), pine (Pinus merkusii), and preserved corn (Zea mays).